Aplikasi Pembelajaran Hand Signals Scuba Diving Berbasis Augmented Reality: Augmented Reality-Based Scuba Diving Hand Signals Learning Application - Henry Valentino Florensius Kainde; Heilbert A. Mapaly; Yuri V. Akay; Lidia S. Nelwan; Michelle W. G. Wowor; Charles W. Kojansow (Universitas Sam Ratulangi, 2024)
Currently, the world is experiencing very rapid development, so that various kinds of technology have emerged that can facilitate the learning process. One of them is augmented reality technology which can allow users to see additional information or virtual images in the real world. The aim of this research is to create a learning application that can help novice divers learn and remember hand signals by utilizing augmented reality technology. Application development uses the Scrum type Agile method which consists of several stages, namely: product blog, sprint planning, sprint, daily scrum, sprint review, and sprint retrospective. In this research, a number of stages have been carried out, namely literature study, data collection, system design and data models, system creation and data processing, testing and evaluation, reporting and publication. The end result of this research is in the form of journals and applications that are made.